2005
DOI: 10.1097/01.olq.0000161089.53411.cb
|View full text |Cite
|
Sign up to set email alerts
|

The Prevalence of Chlamydia, Gonorrhea, and Trichomonas in Sexual Partnerships: Implications for Partner Notification and Treatment

Abstract: In our clinic population, a substantial number of partners had infections different from or in addition to those infections in the index. Many of these infected partners would not be diagnosed and treated using PDPT. Partners of index attendees without detected infection were at high risk (26%) for STI, mostly CT.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
45
0
1

Year Published

2007
2007
2015
2015

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 59 publications
(50 citation statements)
references
References 32 publications
4
45
0
1
Order By: Relevance
“…Analysis of the results verified that 4.4% of men had both infections. The coinfection rate obtained was consistent with the results of previous studies conducted among the male population in Brazil 11,12 and other countries 8,14 .…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…Analysis of the results verified that 4.4% of men had both infections. The coinfection rate obtained was consistent with the results of previous studies conducted among the male population in Brazil 11,12 and other countries 8,14 .…”
Section: Discussionsupporting
confidence: 82%
“…Since male gonococcal infections are largely symptomatic 15 , diagnostic testing, rather than routine screening, has been the recommended disease control strategy, and national disease rates in men reflect mainly symptomatic infection. Although there is evidence that asymptomatic gonococcal infections in heterosexual men may contribute disproportionately to disease transmission to women 14 , relatively few studies have measured the prevalence of Neisseria gonorrhoeae infection among asymptomatic men 9,16,17 . Regarding C. trachomatis infection, the rate of asymptomatic infection is higher 18 .…”
Section: Discussionmentioning
confidence: 99%
“…A couple study by Khan et al [20] found that 11% of partners of persons infected with CT or GC also had TV. Stekler et al [5] found that if EPT was administered to heterosexual persons in Seattle, the potential for 0.4% of HIV and 0.7% of syphilis would be missed and that 10% of CT and GC would be missed among women receiving EPT for TV.…”
Section: Ept: Not a Universal Magic Bulletmentioning
confidence: 98%
“…Igazolt Chlamydia urethritis esetében az után-követés, illetve ismételt kórokozó-kimutatás minden esetben szükséges, tekintettel a tünetmentes hordozás lehetőségére. A gyakori reinfekciók, illetve a nők hosszú távú szövődményeinek tekintetében az ajánlás szerint nőknél 3-4 hónappal az antibiotikumkúrát követően ismételt diagnosztikus vizsgálat végzése tanácsolt [19,20,21,22,23,24].…”
Section: Kezelésunclassified